(3TQM eNJUQ aj eYQaI GdJbGhje GdeNJUQs - (3eMeO Hf eMeO Hf GdMSf, CHh LYaQ, fUjQ GdOjf GdWhSj , J (B672 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdCMhGd ai GdSadjGJ CeG HYO aEf GdeNJUQ GdPi Cdag ai Yde GdfLhe heYQaI GdJbhje GUd ddEeGe GdWhSi s
(3BNQgG (B:s
(3heY Pdc aGdefGSH ddHjY chf GdbeQ efUQakG HgPG GdbOQ MGeOjf deGdc GdbOQ s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B30 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B207s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI WgQGf (B(4901) s
Keywords: (3Gdadcs